Benign chronic pemphigus - new aspects of etiopathogenesis and treatment - Pierzchała, Ewa; Syguła, Ewa; Kamińska-Winciorek, Grażyna; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Benign chronic pemphigus is a rare and dominantly inherited dermatosis characterised by chronic, recurrent progress with predilection to intertriginous areas and characterised by a special histopathological picture. The disease is caused by mutations in ATP2C1 gene, which leads to inappropriate intracellular Ca2+ concentration. Due to a long duration, location and intensification of the disease a few treatment methods are distinguished.